Intellectual Capital and Knowledge Management in Higher Education: Concept, Implementation, and Barriers - Adi Rahmat (AL-ISHLAH: Jurnal Pendidikan, 2022)
Intellectual capital has developed into an intriguing concept that is frequently debated by academics and professionals and has been shown to improve the performance of all types of businesses, including institutions. Through a systematic literature review, this research is expected to enable reflection on the critical role of intellectual capital management in establishing an organization's competitive advantage in higher education and the essential part of knowledge management and socialization opportunities in the development of social thinking in higher education institutions and organizations. Ten articles published in national and international journals were selected to analyze thematically as the research data. The findings report that intellectual capital management lays the groundwork for strategic planning and the commercial success of modern educational institutions. Rethinking processes and fostering knowledge formation, particularly concerning their impact on functional strategies, is critical for academic administrators to increase their competitive advantage, the strength of internal organizational structures, and the effectiveness of educational programs.